Biochemical characterization and mutational analysis of a novel flap endonuclease 1 from Thermococcus barophilus Ch5. (February 2022) - Lin, Tan; Zhang, Likui; Jiang, Donghao; Wu, Leilei; Chen, Kaige; Li, Li; Jin, Cuili; Li, Zheng; Oger, Philippe
Abstract: Flap endonuclease 1 (FEN1) plays important roles in DNA replication, repair and recombination. Herein, we report biochemical characteristics and catalytic mechanism of a novel FEN1 from the hyperthermophilic euryarchaeon Thermococcus barophilus Ch5 (Tb-FEN1). As expected, the recombinant Tb-FEN1 can cleave 5′-flap DNA. However, the enzyme has no activity on cleaving pseudo Y DNA, which sharply contrasts with other archaeal and eukaryotic FEN1 homologs. Tb-FEN1 retains 24% relative activity after heating at 100 °C for 20 min, demonstrating that it is the most thermostable among all reported FEN1 proteins. The enzyme displays maximal activity in a wide range of pH from 7.0 to 9.5. The Tb-FEN1 activity is dependent on a divalent metal ion, among which Mg 2+ and Mn 2+ are optimal. Enzyme activity is inhibited by NaCl. Kinetic analyzes estimated that an activation energy for removal of 5′-flap from DNA by Tb-FEN1 was 35.7 ± 4.3 kcal/mol, which is the first report on energy barrier for excising 5′-flap from DNA by a FEN1 enzyme. Mutational studies demonstrate that the K87A, R94A and E154A amino acid substitutions abolish cleavage activity and reduce 5′-flap DNA binding efficiencies, suggesting that residues K87, R94, and E154 in Tb-FEN1 are essential for catalysis and DNA binding as well. Overall, Tb-FEN1 is an extremely thermostable endonuclease with unusual features.